2001
DOI: 10.1073/pnas.081070898
|View full text |Cite
|
Sign up to set email alerts
|

Cessation of rapid late endosomal tubulovesicular trafficking in Niemann–Pick type C1 disease

Abstract: Niemann-Pick type C1 (NPC1) disease results from a defect in the NPC1 protein and is characterized by a pathological accumulation of cholesterol and glycolipids in endocytic organelles. We followed the biosynthesis and trafficking of NPC1 with the use of a functional green fluorescent protein-fused NPC1. Newly synthesized NPC1 is exported from the endoplasmic reticulum and requires transit through the Golgi before it is targeted to late endosomes. NPC1-containing late endosomes then move by a dynamic process i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
126
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 23 publications
10
126
0
Order By: Relevance
“…5f). Filipin [39][40][41][42] stainings further confirmed a strong accumulation of cholesterol in TPC2 À / À hepatocytes after CD treatment (Fig. 6a).…”
Section: Articlementioning
confidence: 52%
“…5f). Filipin [39][40][41][42] stainings further confirmed a strong accumulation of cholesterol in TPC2 À / À hepatocytes after CD treatment (Fig. 6a).…”
Section: Articlementioning
confidence: 52%
“…In Niemann-Pick C disease, dysfunction of NPC1 results in missorting and accumulation of cholesterol in the late endosomes. The cholesterol loading decreases the capacity of GDI to extract membrane-associated Rab7, thus inhibiting these vesicles from switching from minus-to plusend-directed motility, eventually resulted in a loss of bi-directional motility and paralysis (35,85). Failure to recycle Rab7 to the membrane interferes with the switch in early-to-late endosome maturation and ultimately results in the paralysis of the endocytic system (29,35,60).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that the ability of late endosomes and lysosomes to fuse can depend on lipid accumulation in these compartments (21). To examine this, we evaluated dextran release in cells that had functional NPC proteins but had lysosomal lipid storage disorders.…”
Section: Roles Of Npc1 and Npc2 In The Cellular Efflux Of Membraneimpmentioning
confidence: 99%